2020
DOI: 10.2147/cmar.s232930
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Role of Adjuvant Chemoradiotherapy Over Radiotherapy After R0 Resection for Stage II-III Esophageal Squamous Cell Carcinoma</p>

Abstract: This study compared the effectiveness and safety of postoperative concurrent chemoradiotherapy (POCRT) containing paclitaxel (PTX) and cisplatin (DDP) with postoperative radiotherapy (PORT) after R0 resection for stage II-III thoracic esophageal squamous cell carcinoma (TESCC). Materials and Methods: After propensity score matching (PSM) analysis, 87 TESCC patients treated with PORT were matched 1:1 to 87 patients who received POCRT between July 2012 and December 2018. Radiotherapy was delivered at a dose of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 23 publications
1
16
1
Order By: Relevance
“…In contrast, Zhang et al [ 26 ] examined patients with TNM stage II/III ESCC and showed that the OS was significantly worse for those who received sequential POCRT rather than PORT or concurrent POCRT. Zou et al [ 27 ], Hsu et al [ 28 ], and Song et al [ 9 ] showed that POCRT significantly increased OS and DFS compared with PORT in patients with pN+ ESCC. The present study also found that POCRT significantly improved OS ( p = 0.034) and DFS ( p = 0.009) compared with POCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Zhang et al [ 26 ] examined patients with TNM stage II/III ESCC and showed that the OS was significantly worse for those who received sequential POCRT rather than PORT or concurrent POCRT. Zou et al [ 27 ], Hsu et al [ 28 ], and Song et al [ 9 ] showed that POCRT significantly increased OS and DFS compared with PORT in patients with pN+ ESCC. The present study also found that POCRT significantly improved OS ( p = 0.034) and DFS ( p = 0.009) compared with POCT.…”
Section: Discussionmentioning
confidence: 99%
“…A systemic review by Liu et al [ 23 ] concluded that PORT clearly reduced the risk of LR in patients with ESCC. Song et al [ 9 ] reported that POCRT, relative to PORT, administered to patients with pN+ ESCC significantly decreased DM. In contrast, our results and the results of Zou et al [ 27 ] indicated no significant differences in recurrence or DM in groups that received POCRT and PORT.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Li et al [ 10 ], gender showed a significant association with OS and DFS on univariate analysis but not on multivariate analysis. However, in other studies [ 11 , 22 , 25 ], gender was not associated with OS in ESCC patients after surgery.…”
Section: Discussionmentioning
confidence: 70%
“…In several studies, clinical stage was an independent prognostic factor for OS and DFS in patients with II-III ESCC [ 10 , 11 , 22 , 23 ]. In other studies, pT and pN were independent prognostic factors for OS and DFS [ 17 , 22 , 24 – 26 ]. In the study by Ni et al, OS and DFS were significantly different between stages IIIb and IIIc, but not between IIIa and IIIb on univariate analysis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation